Modeling large deformations in water retention structures with an unsaturated MPM approach. Issue 3 (14th June 2021) - Girardi, Veronica; Yerro, Alba; Ceccato, Francesca; Simonini, Paolo
Abstract : To conduct landslide risk assessment and assess the consequences of dam and levee failures, it is important to understand the overall failure evolution process that ranges from small-strain initiation to large-strain post-failure runout. To achieve this goal and simulate such landslide events, emerging large-strain numerical approaches, such as the Material Point Method (MPM), show promising potential as tools to model the entire instability mechanism. While successfully incorporating multi-phase interactions in granular porous media. Soil-water interaction in unsaturated soils is critical when dynamic hydraulic loads act on levees, such as when the fluvial upstream water levels oscillate and in episodes of heavy rainfall infiltration. Recently, MPM has been successfully used in many geotechnical engineering applications, which in turn motivated further advancements of multi-phase formulations. This study presents an application of a novel Single-Point 2-Phase MPM formulation to model unsaturated soils subjected to transient hydraulic boundary conditions. The potential of this approach is discussed by analyzing a large-scale slope failure experiment. Results are compared with the Finite Element Method (FEM) and Limit Equilibrium Method (LEM). We conclude that similar results are obtained at small strains, but MPM allows to estimate the post-failure behaviour, which is essential for risk management.